Rational-security and fair two-party comparison protocol - Bowen ZHAO; Yao ZHU; Yang XIAO; Qingqi PEI; Xiaoguo LI; Ximeng LIU (Tongxin xuebao)
Existing secure two-party comparison protocols usually allowed one party (e.g., Alice) to obtain a comparison result first, and then Alice informed the other one (e.g., Bob) of the comparison result.Obviously, if Alice refused or failed to send the comparison result to Bob, Bob learned nothing about the comparison result, which broke the fairness of the two-party comparison protocol.Based on this, a rational-security and fair two-party comparison protocol TEAM was proposed by seamlessly combining the threshold Paillier cryptosystem and game theory.Specifically, a novel secure two-party comparison protocol based on the threshold Paillier cryptosystem was designed and then searched for equilibrium points at which two parties could obtain comparison results.Strict theoretical analysis demonstrate that TEAM guarantees rational two-party to always obtain the comparison result without sacrificing any of their inputs.In other words, TEAM was correct, secure, and fair.In addition, the experimental results show that TEAM improves up to 50 times in terms of efficiency compared with previous methods under the same experimental settings.